Pengaruh Literasi Keuangan, Pengalaman Keuangan dan Gaya Hidup terhadap Perilaku Mengelola Keuangan Usaha Mikro Kecil (UMK) - Lismarisa, Nora; Wening, Nur; Sujoko, Sujoko (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study is motivated by the phenomenon that many micro and small business actors are trapped in easy online loans but pay high interest. In addition, in the business they own, product pricing is oriented towards general conditions so that labor costs are rarely taken into account. As a result, they often make mistakes in measuring business productivity which ultimately leads to business decline. The problems that are often faced are more in financial management due to low financial literacy, lack of experience in finance and lifestyle. This study aims to test and analyze the influence of financial literacy, financial experience and lifestyle on the financial management behavior of MSE’s actors. Data were obtained from questionnaires to 100 respondents which were processed using multiple linear regression analysis. The results of the study stated that financial literacy, financial experience have a positive and significant effect on financial management behavior while lifestyle does not have a significant effect on financial management behavior.